Manajemen Inovasi Pendidikan di Sekolah Dasar - Kusman, Muhammad (JIEM (Journal of Islamic Education Management), 2020)
This research was intended to reveal in-depth the management of educational innovations in the Islamic Primary Full Day School Cahaya Qolbu Subang. This research was a qualitative field research. Data collection techniques used in-depth observation, in-depth interviews, and documentation. Data analysis techniques were carried out through inductive analysis methods to draw conclusions about events or things from the data that have been collected, and compare them and then generalize or be drawn towards general conclusions. Data analysis techniques were done through inductive analysis methods to make conclusions from the collected data, and compare them then generalize them or conclude them in general. The research findings showen that the management of educational innovations was carried out through the process of management of school resources to realize educational goals through curriculum innovations applying correlated curriculum, human resource innovation through personnel management. Learning innovation was done by integration between curriculum of school and madrasa. This innovation emphasized integration in the application of learning methods to maximize all student domains and integrate active participation and involvement in the learning environment, namely schools, homes and communities.